Scientific authorship: a primer for researchers - Olena Zimba (Termedia Publishing House, 2020)
The International Committee of Medical Journal Editors (ICMJE) proposed the authorship criteria which can be employed by medics and allied specialists. Scholars who substantively contribute to research and writing, revise, approve final drafts for target journal submissions, and take responsibility for all aspects of the work deserve authorship. Increasing awareness of the ICMJE criteria, incorporating related points in journal instructions, and enforcing them in daily practice may have positive impact for healthcare. Instances of inappropriate authorship are ethical transgressions which can be avoided by editors employing strategies of author profile evaluations. There are several platforms for recording author accomplishments which may improve the discoverability of scholarly works and prevent unethical conduct. Most publishers advise authors to submit their Open Researcher and Contributor IDs (ORCID) at the manuscript submission. Other identifiers, such as Twitter handles, are also emerging as tools to stimulate post-publication communication and increase authors’ accountability for published articles.